2021
DOI: 10.3390/ijms22041607
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII and Fibrin Clot Properties in Acute Venous Thromboembolism

Abstract: Coagulation factor XIII (FXIII) is converted by thrombin into its active form, FXIIIa, which crosslinks fibrin fibers, rendering clots more stable and resistant to degradation. FXIII affects fibrin clot structure and function leading to a more prothrombotic phenotype with denser networks, characterizing patients at risk of venous thromboembolism (VTE). Mechanisms regulating FXIII activation and its impact on fibrin structure in patients with acute VTE encompassing pulmonary embolism (PE) or deep vein thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…A hypercoagulable state was observed in both the patients with a high level of VWF and VWF:RCo, D-dimer, and coagulation Factor VIII. Factor XIII was markedly decreased in patient 1, probably due to excessive consumption within thrombi 19 .…”
Section: Discussionmentioning
confidence: 92%
“…A hypercoagulable state was observed in both the patients with a high level of VWF and VWF:RCo, D-dimer, and coagulation Factor VIII. Factor XIII was markedly decreased in patient 1, probably due to excessive consumption within thrombi 19 .…”
Section: Discussionmentioning
confidence: 92%
“…Factor XIII was markedly decreased in patient 1, probably due to excessive consumption within thrombi. 10 Treatment of this new syndrome is challenging. Administration of high-dose IVIg has been suggested in attempt to inhibit Fcγ receptor-mediated platelet activation, since in the treatment of severe autoimmune HIT this treatment resulted in rapid increase in platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…The FGB rs1800790 polymorphism was also found to prolong CLT and promote thinner fibrin fibres formation in patients with type 2 diabetes mellitus 16 . In several studies, F13 rs5985 T allele has been shown as a ‘protective’ genetic factor associated with a lower risk of VTE 10,17–19 . The protection has been suggested to be linked to high fibrinogen levels, 19 which in association with F13 rs5985 T allele predisposed to the formation of thicker fibrin fibres, increased K s and susceptibility to lysis.…”
Section: Introductionmentioning
confidence: 99%
“…16 In several studies, F13 rs5985 T allele has been shown as a 'protective' genetic factor associated with a lower risk of VTE. 10,[17][18][19] The protection has been suggested to be linked to high fibrinogen levels, 19 which in association with F13 rs5985 T allele predisposed to the formation of thicker fibrin fibres, increased K s and susceptibility to lysis. On the contrary, individuals with normal fibrinogen levels, F13 rs5985 T allele carriers, are characterized by thinner fibrin fibres and reduced K s , which may be due to faster FXIII activation and faster fibrin cross-linking.…”
Section: Introductionmentioning
confidence: 99%